ACADEMIC STRESS AND PERCEIVED SOCIAL SUPPORT IN CHILDREN AND ADOLESCENTS WITH AND WITHOUT SPECIFIC LEARNING DISABILITIES: A COMPARATIVE STUDY - Tehmina Jabeen; Rauf, Khalida (Pakistan Journal of Clinical Psychology, 2023)
Objectives: This study investigated the relationship between perceived social support and academic stress among Children and Adolescents with and without Specific learning disabilities. Design of study: Quantitative survey based approach, with comparative research design. Place of the study: Karachi, Pakistan. Sample and method: Purposive sampling technique was used to select N= 60 learning and non-learning disabled individuals between 6 to 17 years. Multidimensional Scale of Perceived Social Support and Academic Stress Scale were used for data collection. Results were analysed using descriptive statistics and to find the difference between the two groups on academic stress and social support t test for independent sample was calculated. Correlation and linear regression were calculated to study the relationship and estimate the effects between variables academic stress and perceived social support. Results and Conclusion: Significant differences on the levels of Perceived Social Support (p<0.05) and Academic Stress (p<0.05) between the two groups were observed. Furthermore, there was significant relationship (p<0.01) between perceived family support and academic stress in individuals with learning disabilities. In order to find the predictive role of the factors regression analysis was carried out.